A Rh-catalyzed 1, 2-sulfur migration/aza-Diels–Alder cascade initiated by aza-vinyl carbenoids from sulfur-tethered N-sulfonyl-1, 2, 3-triazoles. Issue 11 (23rd December 2014) - Jiang, Yu; Tang, Xiang-Ying; Shi, Min
Abstract : A novel Rh(ii ) catalyzed intramolecular 1, 2-sulfur migration/intermolecular aza-Diels–Alder cascade of sulfur-tethered N -sulfonyl-1, 2, 3-triazoles has been developed, efficiently affording sulfur-containing tetrahydropyridine derivatives. Abstract : A novel Rh(ii ) catalyzed intramolecular 1, 2-sulfur rearrangement/intermolecular aza-Diels–Alder cascade initiated by azavinyl carbenes has been developed, efficiently affording sulfur-containing tetrahydropyridine derivatives or α, β-unsaturated imines with a broad substrate scope.